Bioenergetic profile of tennis singles match play - Baiget, E.; Iglesias, X.; Rodriguez, F. A. (Archivos de medicina del deporte, 2008)
This study aims to characterize the metabolic response during tennis singles match play in order to establish a bioenergetic profile of male singles tennis competition. Materials and methods: 20 male competitive players (4 ATP, 16 ITN 1-4) participated in 10 tennis singles matches to the best in two sets. Games were played on average-speed hard surface (Green Set). Ventilatory and gas exchange parameters were measured with a portable breath-by-breath gas analyser (K4 b2, Cosmed, Italy). Between 2 and 7 days afterwards subjects performed a specific endurance tennis test (SET-Test) using the same analyser. During the incremental test the fi rst (VT1) and second (VT2) ventilatory thresholds were identified. Results: A total of 20 sets and 170 games were played. Average set duration was 31:03 +/- SD 11:23 min:s. Average VO2 values of 29.9 +/- 3.7 mL/kg min-1 (51.6 +/- 8.6 % of VO2max) were measured. The players exercised 77.2 +/- 24.5 % of the time (22:14 ± 08:26 min:s) at an intensity below AT1; 20.0 ± 21.2 % (07:14 ± 09:25 min:s) was played between VT1 and VT2; only 2.9 ± 4,7 % (01:00 ± 01:55 min:s) time was played over AT2. Conclusions: The moderate VO2 values suggest that the oxygen transport system is not a limiting factor for tennis performance. Since players spend a lot of time at rest between points (77.9 %), the average intensity during most of the actual playing time is moderate (i.e. within the aerobic-anaerobic transition phase), although interspersed with the characteristic explosive actions. Playing phases over the respiratory compensation point (i.e. causing lactic acidosis) are minimal, although they might happen at crucial moments during the game.